ANALISIS PEMBELAJARAN PENDIDIKAN AGAMA ISLAM TERHADAP PEMBENTUKAN MORAL SISWA KELAS IV DI SDN 4 CILANGKAP - Sansan Khaulatul Wardah; Ahmad Mulyadi Prana; Anggi Maulana Rizqi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study investigates the role of Islamic Religious Education (PAI) in shaping themoral development of fourth-grade students at SDN 4 Cilangkap. The researchstems from growing concerns regarding moral degradation among elementarystudents, which manifests through impolite behavior, dishonesty, and a lack ofrespect towards teachers and peers. The study aims to (1) describe theimplementation of PAI in the classroom, (2) analyze the moral behavior ofstudents, and (3) identify supporting and inhibiting factors in moral development.Using a qualitative descriptive approach, data were collected through observation,interviews, and documentation. The findings reveal that while the school hasimplemented regular religious activities such as communal prayers, Quranrecitation, and Islamic values integration in daily routines, students still facechallenges in internalizing moral values. Influencing factors include the role ofparents, teachers, school culture, and external influences such as media and peerinteraction. The study concludes that although the PAI curriculum plays a vital rolein promoting moral awareness, its effectiveness is contingent upon consistency inapplication and collaboration between school and home environments. Therefore,for Islamic education to effectively shape student morality, it must be reinforcedthrough a holistic approach involving structured learning, character-basedpractices, and active moral modeling by educators and parents alike.